2009
DOI: 10.1016/j.bcp.2009.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the anthelmintic drug PF1022A on mammalian tissue and cells

Abstract: Nematode infections cause human morbidity and enormous economic loss in livestock. Since resistance against currently available anthelmintics is a worldwide problem, there is a continuous need for new compounds. The cyclooctadepsipeptide PF1022A is a novel anthelmintic that binds to the latrophilin-like transmembrane receptor important for pharyngeal pumping in nematodes. Furthermore, PF1022A binds to GABA receptors, which might contribute to the anthelmintic effect. Like other cyclodepsipeptides, PF1022A acts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Our observations, and previous reports, indicate that the modulation of the Ca 2+ -activated K + channels in HEK293 cells by emodepside cannot be ascribed to an elevation of intracellular Ca 2+ . The parent compound for emodepside, the cyclooctadepsipeptide PF1022A, does not increase intracellular Ca 2+ in CaCo-2 cells [ 34 ]. Here we conducted a similar study on HEK293 cells and showed that a supramaximal concentration of emodepside (100μM) had no significant effect on the intracellular concentration of Ca 2+ .…”
Section: Discussionmentioning
confidence: 99%
“…Our observations, and previous reports, indicate that the modulation of the Ca 2+ -activated K + channels in HEK293 cells by emodepside cannot be ascribed to an elevation of intracellular Ca 2+ . The parent compound for emodepside, the cyclooctadepsipeptide PF1022A, does not increase intracellular Ca 2+ in CaCo-2 cells [ 34 ]. Here we conducted a similar study on HEK293 cells and showed that a supramaximal concentration of emodepside (100μM) had no significant effect on the intracellular concentration of Ca 2+ .…”
Section: Discussionmentioning
confidence: 99%
“…A similar train of thought suggests that at micromolar concentrations of emodepside, a concentration that is difficult to keep in aqueous solution, emodepside would appear in the membrane at a 1:1 emodepside/lipid ratio where one might expect to see additional membrane perturbant effects. Indeed, this expectation is realised by the report that the parent compound of emodepside, PF1022A, has ionophore properties and directly confers ion channel activity on membranes, although this appears unrelated to its anthelmintic action (Geßner et al 1996; Dornetshuber et al 2009).
Fig.
…”
Section: Clues To the Mode Of Action Based On The Time-course Of Actimentioning
confidence: 99%
“…Quantification of the neurotoxic potential of EMO in PGP mut and PGP WT mice on the rotarod Next, we aimed to elucidate whether the increased brain penetration of EMO in the PGP mut mice may provoke neurological toxicity. As data about an interaction of EMO with vertebrate receptors are limited (Dornetshuber et al, 2009;Crisford et al, 2011), it was not clear which kind of effects could be expected in the case of EMO-induced neurological toxicity in mice. Repeated oral dose toxicity studies in rats and mice revealed effects on the neurological function, behavior, ataxia, and increased motility.…”
Section: Brain Penetration Of Emo Is Increased In Pgp Mut Micementioning
confidence: 99%
“…It is well established that EMO exhibits high antiparasitic efficacy even in multiresistant parasite strains and low toxicity in mammals (Conder et al, 1995;von Samson-Himmelstjerna et al, 2000;Harder et al, 2003Harder et al, , 2005Jeschke et al, 2005;Dornetshuber et al, 2009). During approval of this new drug entity, EMO was identified as a substrate of P-glycoprotein (Pgp) which is coded by the multidrug resistance gene (MDR1) (syn.…”
Section: Introductionmentioning
confidence: 99%